OP-5 INTEROBSERVER VALIDITY OF THE REFLUX FINDING SCORE FOR INFANTS (RFS-I) IN FLEXIBLE VERSUS RIGID LARYNGOSCOPY. Issue 4 (October 2015) - Singendonk, MMJ; Pullens, B; van Heteren, JAA; de Gier, HHW; Hoeve, HJ; König-Jung, AM; van der Schroeff, MP; Hoekstra, CEL; Veder, LL; van der Pol, RJ; Benninga, MA; van Wijk, MP
Abstract : Background: The Reflux Finding Score for Infants (RFS-I) was developed to objectively assess signs of laryngopharyngeal reflux (LPR). Based on review of flexible laryngoscopic videos, only moderate inter- and highly variable intraobserver reliability was found. We hypothesized that examination of the infant larynx with rigid laryngoscopy would provide better agreement. AIM: to assess the validity of the RFS-I in the detection of LPR-related findings using flexible versus rigid laryngoscopy. Methods: Thirty consecutive infants underwent flexible and rigid laryngoscopy. Based on the recorded videos, RFS-I was scored by 4 otorhinolaryngologists, 2 otorhinolaryngology fellows, and 2 inexperienced observers. Videos were presented in a randomized order, blinded for clinical profile and findings during initial examination. Observers were provided an instruction sheet prior to evaluation. For categorical data, agreement was calculated using Cohen's kappa (2 observers) and Fleiss' kappa (>2 observers). For ordinal data the intraclass correlation coefficient (ICC) was used. Results: Of 30 included patients (17 M; median age 7.5 (0–19.8) months), main reasons for referral were: stridor (n = 15, 50%), ALTE/apneas (n = 7, 23.3%), follow-up of laryngeal abnormalities (n = 6, 20%), aspiration (n = 5, 16.7%), and other indications (n = 7, 23.3%). Overall interobserver agreement of the RFS-I was moderate for both flexible (ICC = 0.60, [95%CI 0.44–0.76]) and rigid (ICC = 0.42, [95%CI 0.26–0.62] laryngoscopy. There were no significant differences in agreement on overall RFS-I scores and individual RFS-I items for flexible versus rigid laryngoscopy. We did observe higher overall agreement amongst the 2 inexperienced observers for rigid (ICC = 0.40, [95%CI 0.03–0.67]), compared to flexible (ICC = 0.11, [95%CI 0.17–0.41]) laryngoscopy, albeit not significant. Comparing RFS-I results for flexible versus rigid laryngoscopy per observer, agreement ranged from no to substantial agreement ( k   =  -0.16–0.63, mean k  = 0.22) and the observed agreement (not adjusted for chance) was 0.08–0.35%. Conclusions: Interobserver agreement of the RFS-I was only moderate and did not differ between flexible and rigid laryngoscopy. This indicates that the RFS-I should not be used with flexible, nor rigid laryngoscopy to detect signs of LPR.